Retina stem cells, hopes and obstacles - German, Olga Lorena (2021)
Retinal degeneration is a major contributor to visual dysfunction worldwide. Although it comprises several eye diseases, loss of retinal pigment epithelial (RPE) and photoreceptor cells are the major contributors to their pathogenesis. Early therapies included diverse treatments, such as provision of anti-vascular endothelial growth factor and many survival and trophic factors that, in some cases, slow down the progression of the degeneration, but do not effectively prevent it. The finding of stem cells (SC) in the eye has led to the proposal of cell replacement strategies for retina degeneration. Therapies using different types of SC, such as retinal progenitor cells (RPCs), embryonic SC, pluripotent SCs (PSCs), induced PSCs (iPSCs), and mesenchymal stromal cells, capable of self-renewal and of differentiating into multiple cell types, have gained ample support. Numerous preclinical studies have assessed transplantation of SC in animal models, with encouraging results. The aim of this work is to revise the different preclinical and clinical approaches, analyzing the SC type used, their efficacy, safety, cell attachment and integration, absence of tumor formation and immunorejection, in order to establish which were the most relevant and successful. In addition, we examine the questions and concerns still open in the field. The data demonstrate the existence of two main approaches, aimed at replacing either RPE cells or photoreceptors. Emerging evidence suggests that RPCs and iPSC are the best candidates, presenting no ethical concerns and a low risk of immunorejection. Clinical trials have already supported the safety and efficacy of SC treatments. Serious concerns are pending, such as the risk of tumor formation, lack of attachment or integration of transplanted cells into host retinas, immunorejection, cell death, and also ethical. However, the amazing progress in the field in the last few years makes it possible to envisage safe and effective treatments to restore vision loss in a near future.